DAMPAK OVERCAPACITY TERHADAP TINGKAT STATUS GIZI NARAPIDANA - Isjwara, Faiz Fakhri (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2020)
The principle of the organization of prisons (Lembaga Pemasyarakatan/ LAPAS) must prioritize a humane approach so that prisoners and prisoners receive their rights. If the implementation is good, the objective of LAPAS is to carry out social reintegration, namely the restoration of the unity of life, life and livelihood of prisoners and correctional students both prisoners as individuals, social beings and God's creatures with society can be achieved. However, this organization faces obstacles, namely the problem of overcapacity. This can have implications for suboptimal and can even lead to failure to function as a correctional institution. The problem of over capacity will also have an impact on the health conditions of prisoners. Sleep conditions, eating patterns, health services that are less than the maximum due to over capacity will certainly have a negative impact on the nutritional status of prisoners. This study aims to determine the impact of Overcapacity Impacts on the Nutritional Status Level of Prisoners in Class II A Penitentiary, Sidoarjo. This type of research is a quantitative correlational analytic survey with a cross-sectional design. The number of samples was 91 inmates. The sampling technique is by random sampling. Data is collected by weighing body weight and height and comparing with ideal body weight. The results showed that the more overcapacity, the nutritional status of prisoners decreased. Room conditions can affect the provision of an unbalanced diet. Thus, that this causes the prisoners to experience malnutrition.